МУАЛЛИФ СЕМАНТИК ТИЗИМИНИ АНИҚЛАШДА БАДИИЙ КОНЦЕПТЛАРНИНГ РОЛИ - Халимова, Ф.Р. (SCIENCE and SOCIETY, 2023)
Since the semantics of a poetic text consists of words of connotative content, artistic concepts, its logic and affectivity also increase to this extent. The poet’s use of certain specific words determines his individuality. The pragmatic potential of the poem depends on the originality of the author. The role of artistic concepts, that is, the conceptual system of a poetic text, is significant in determining the semantic potential of the author.
Keywords: concept; conceptual field; literary concept; idiostyle; semantic system